164k views
2 votes
I need help on number 2 I need explanation will give ⭐️⭐️⭐️⭐️⭐️ if you give a good explanation

I need help on number 2 I need explanation will give ⭐️⭐️⭐️⭐️⭐️ if you give a good-example-1
User Dave Reid
by
5.9k points

1 Answer

5 votes

Note that in the statement of the exercise are the values of j, k, and l. Then, to evaluate the given expression, we replace the given values of j, k, and l. So, we have:


\begin{gathered} j=9 \\ k=4.5 \\ l=3 \\ \mleft(j-2\mright)^3+k\text{ }/ l=(j-2)^3+(k)/(l) \\ \text{ We replace the know values} \\ (9-2)^3+(4.5)/(3)=7^3+1.5 \\ (9-2)^3+(4.5)/(3)=7\cdot7\cdot7+1.5 \\ (9-2)^3+(4.5)/(3)=343+1.5 \\ (9-2)^3+(4.5)/(3)=\boldsymbol{344.5} \end{gathered}

Therefore, the result of evaluating the given expression is 344.5.

User David Marx
by
5.8k points